Surprise Without a Cause?. ‘False Recapitulations’ in the Classical Repertoire and the Modern Paradigm of Sonata Form - Markus Neuwirth (Zeitschrift der Gesellschaft für Musiktheorie)
False recapitulations are often cited as a hallmark of Joseph Haydn’s sonata-form style, exemplifying perhaps better than any other technique the composer’s witty and subversive engagement with formal conventions. However, closer scrutiny reveals that the concept of false recapitulation is based on a number of different, partially incompatible cognitive, intentional, theoretical, and historical criteria. In an attempt to reconstruct the horizon of expectations of historical listeners, I shall essentially draw on two sources: the compositional practice of the time as reflected in a preliminary repertoire study and contemporaneous theoretical writings. In a nutshell, I shall argue that the analytical practice of framing a double return in the development section in terms of a play with listener expectations is based on the anachronistic assumptions of what I call the “modern paradigm of sonata form”. Placing expectations at the center of analysis and scrutinizing its complex preconditions allows us to arrive at a refined understanding of Haydn’s (and others’) usage of supposedly false recapitulations.